Cities and Their People: Dwelling in the Anthropic Time of N. K. Jemisin’s New York - Sugiera, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2024)
The article starts with Martin Heidegger’s 1951 essay “Bauen Wohnen Denken,” recently rethought by Jeff Malpas in his book Rethinking Dwelling from today’s perspective of urban and metropolitan dwelling. However, while defining dwelling relationally, the Australian philosopher still thinks about the human as a being-in-place in a traditional, human-centred way. Thus he overlooks how tightly humans are entangled with more-than-humans: with biological, geological, and technological entities and agencies. For this reason, the article tackles a further rethinking of dwelling beyond human sociality, or even queering it beyond binary thinking to better depict what it proposes to call urban subjectivity. Reading N. K. Jemisin’s recent novel duology The Great Cities, the article argues that urban subjectivity is a distributed phenomenon, which both incorporates and elaborates on more-than-human elements. In so doing, urban subjects share a sociality not only with the animal and geological but also with technological forces and their territorial exorganic functions as an agency of anti-entropic locality (Bernard Stiegler’s “anthropic life”). Thus, creatively approached technology as a pharmakonian form of organogenesis and Derridian différance may help us keep the entropic and neganthropic forces in balance, as pertinently demonstrated in Jemisin’s duology.